Total Pancreaticoduodenectomy and Segmental Resection of Superior Mesenteric Vein-Portal Vein Confluence with Autologous Splenic Vein Graft in Mucinous Cystadenocarcinoma of the Pancreas - Choi, Sung Hoon; Hwang, Ho Kyoung; Kang, Chang Moo; Lee, Woo Jung (JOP. Journal of the Pancreas, 2010)
Context Mucinous cystic tumors occur almost exclusively in middle-aged women and in the body or tail of the pancreas. Mucinous cystadenocarcinoma, a malignant sub-type of mucinous cystic tumors, in the head of the pancreas and in a middle-aged man is extraordinary, and the prognosis and proper management of mucinous cystadenocarcinoma has not been well documented. Case report A 52-year-old male patient with a mucinous cystadenocarcinoma approximately 5.5 cm in size in the head of the pancreas underwent a total pancreaticoduodenectomy and segmental resection of the superior mesenteric vein-portal vein confluence with an autologous splenic vein graft due to tumor invasion. His postoperative course was uneventful and he received adjuvant chemotherapy. He has been followed-up periodically for more than 30 months after surgery without evidence of recurrence. Conclusion Mucinous cystadenocarcinoma in the head of the pancreas in a middle-aged man is an extremely rare case. Because mucinous cystadenocarcinomas have a relatively good prognosis, an aggressive approach with major vascular resection is warranted in well-selected patients. Splenic vein interposition grafting could be used in cases which undergo total pancreaticoduodenectomy with segmental resection of the superior mesenteric vein-portal vein confluence if the splenic vein is healthy. Image: Preoperative studies.